Impact of feeding volumes in the first 24 h of life on neonatal feeding intolerance - Kumar, Navin; Oredein, Igbagbosanmi; Al-Nahar, Mohammed; Harris, Nathalee; Sampath, Venkatesh (Frontiers in Pediatrics, 2023)
OBJECTIVE: Whether volumes of intake in the 1st 24 hours of life (24 HOL), in relation to birth weight (BW) and gestational age (GA), impacts neonatal feeding intolerance (FI) has not been well quantified and was investigated herein. METHODS: Retrospective chart review of 6650 infants born at ≥ 35 weeks. Volumes of each formula feed per kg BW, in the 1st 24 HOL, were assessed. FI was defined as evidenced by chart documentation of emesis, abdominal distension, abdominal x-ray, and/or switching to a sensitive formula. RESULTS: Overall, the maximum volume of formula intake per feed was inversely correlated with GA and was higher with FI (β = -1.39, p<0.001) vs no FI (β = -1.28, p<0.001). Odds of, emesis in late preterm infant with 1st feeding of >8 ml/kg [AOR = 2.5, 95% (CI 1.4-4.6)], and formula switching in exclusive formula fed group with volumes > 10.5 ml/kg [AOR= 2.2, 95% CI (1.8-2.6)] was higher. In breastfeeding group, odds of FI increased by 2.8-, 4.6-, and 5.2-fold with 5-10, 10-15, and >15ml/kg of supplementations, respectively. CONCLUSION: Higher volume of intake in relation to BW, often exceeds physiological newborn stomach capacity and is associated with early FI. Optimizing early feeding volumes accounting for infants BW and GA may decrease a good proportion of FI as they may, in reality, be a volume intolerance issue.